2014
DOI: 10.1007/s10571-014-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt Phosphorylation Diminishes Mitochondrial Biogenesis Regulators, Tricarboxylic Acid Cycle Activity and Exacerbates Recognition Memory Deficit in Rat Model of Alzheimer’s Disease

Abstract: 3-Methyladenine (3-MA), as a PI3K inhibitor, is widely used for inhibition of autophagy. Inhibition of PI3K class I leads to inhibition of Akt phosphorylation, a central molecule involved in diverse arrays of intracellular cascades in nervous system. Accordingly, in the present study, we aimed to determine the alterations of specific mitochondrial biogenesis markers and mitochondrial function in 3-MA-injected rats following amyloid beta (Aβ) insult. Our data revealed that inhibition of Akt phosphorylation down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…This suggests that AMPK activation is associated with autophagy induction, which is involved in the process of MTAinduced odontoblastic differentiation of dental pulp cells. A similar result reported that p-AMPK levels declined in the 3MA-administrated rat model of Alzheimer leads to reduced neurogenesis and induced memory deficit (Shaerzadeh et al 2014 Reparative dentine formation is an important process in the recovery of the pulp-dentine complex (Goldberg & Smith 2004, Charadram et al 2012. When injuries of dentine occur, subjacent HDPCs are attracted to the damaged site and undergo odontogenic differentiation to form new dentine.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This suggests that AMPK activation is associated with autophagy induction, which is involved in the process of MTAinduced odontoblastic differentiation of dental pulp cells. A similar result reported that p-AMPK levels declined in the 3MA-administrated rat model of Alzheimer leads to reduced neurogenesis and induced memory deficit (Shaerzadeh et al 2014 Reparative dentine formation is an important process in the recovery of the pulp-dentine complex (Goldberg & Smith 2004, Charadram et al 2012. When injuries of dentine occur, subjacent HDPCs are attracted to the damaged site and undergo odontogenic differentiation to form new dentine.…”
Section: Discussionmentioning
confidence: 67%
“…A similar result reported that p‐AMPK levels declined in the 3MA‐administrated rat model of Alzheimer leads to reduced neurogenesis and induced memory deficit (Shaerzadeh et al . 2014). Additionally, mTOR phosphorylation and ULK1 phosphorylation at Ser 757 were moderately decreased, but ULK1 phosphorylation at Ser 317 was largely increased in MTA‐treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K can then phosphorylate Akt/PKB. Inhibition of Akt phosphorylation exacerbates memory deficits in a rat model of Alzheimer's disease ( 39 ). Thus, activation of PI3K may be inhibited by sevoflurane and thereby decrease levels of phosphorylated Akt, as well as inhibit cleavage of pro-BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…These divergent findings may reflect different stages of AD progression. In an animal model of AD, it was demonstrated that the inhibition of mitochondrial biogenesis regulators is associated with the inhibition of Akt phosphorylation [166]. In the same mouse model, Zhang et al [167] reported that neural stem cell transplantation enhances mitochondrial biogenesis.…”
Section: Impaired Mitochondrial Biogenesismentioning
confidence: 99%